Padrões funcionais e de concordância de espécies comuns e raras. - Paula, Aline Caroline Magro de (2020)
Dividing communities into common and rare species, we can understand the processes that structure and determine the distribution of species. Based on this principle, the effect of spatial, environmental and temporal processes on the composition and abundance of common and rare species from different taxonomic groups (phytoplankton, zooplankton and fish) was evaluated in this work. It was also simulated, as the stability of ecosystem functions, considered as the number of phytoplankton functional groups (GFRs), will be affected by the extinction of common and rare species of phytoplankton. To this end, a long series of data (17 years old), obtained in the floodplain of the upper Paraná River, was analyzed. We sought to answer whether sets of common and rare species are most affected by spatial and / or niche processes and whether they are concordant between taxonomic groups and between common and rare species and also if they are dependent on the criterion used to define rarity. The results obtained indicated that the relative contribution of each process varies according to the taxonomic group, but does not vary according to the criterion to define rarity. Both spatial and environmental factors were important for communities, but environmental ones prevailed, especially for common species. It was also examined how the extinction of species (common and rare) affects the stability of ecosystem functions (number of GFRs). The simulated species loss scenarios showed that the phytoplankton functional richness is more affected by the loss of common species than by rare species, both in the high and low water periods. It has also been shown that unconnected lentic environments have a greater contribution from common species, being more affected by the loss of these species.